2009
DOI: 10.1097/coh.0b013e328331dea5
|View full text |Cite
|
Sign up to set email alerts
|

Defining treatment failure in resource-rich settings

Abstract: Purpose of review-To define treatment failure in resource-rich settings; summarizing current guidelines, assays, the significance of detectable viremia, and definitions of treatment failure in clinical and research settings.Recent findings-The goal of treatment should be full viral suppression, even in highly treatment experienced patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 52 publications
0
42
1
2
Order By: Relevance
“…Our definition of viremia was based on a single prescan HIV plasma RNA measurement of >200 copies/mL as per the latest US Department of Health and Human Services guidelines [18, 19]. …”
Section: Methodsmentioning
confidence: 99%
“…Our definition of viremia was based on a single prescan HIV plasma RNA measurement of >200 copies/mL as per the latest US Department of Health and Human Services guidelines [18, 19]. …”
Section: Methodsmentioning
confidence: 99%
“…Those around the current limit of detection of 50 copies/ml and that occur only once may not be predictors of future failure 45 copies/ml, will be deleterious. A previous study suggested a significant increase in risk of virological failure in patients whose EIV is over 120 copies/ml.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Immunological criteria were two times more sensitive than clinical criteria in the current and previous studies, supporting the concept that immunological failure occurs earlier than clinical failure. [13] When a combination of clinical and immunological criteria was used, the sensitivity and specificity to predict virological failure were 25.8% and 69.9%, respectively. The combination of clinical and immunological criteria therefore had higher sensitivity but relatively low specificity in predicting virological failure, i.e.…”
Section: Discussionmentioning
confidence: 99%